(untitled) (Journal of the College of Basic Education, 2022)
In this paper, a method for solving linear system of Volterra integro – differential equation of the first order numerical presented based on Monte –Carlo techniques. Numerical examples illustrate the pertinent features of the method with the proposed system. The computer program are written in (TURBO MATLAB) language (Version 6).